2002
DOI: 10.1016/s0014-5793(02)03775-4
|View full text |Cite
|
Sign up to set email alerts
|

Engineering of Escherichia coli β‐galactosidase for solvent display of a functional scFv antibody fragment

Abstract: Protein engineering allows the generation of hybrid polypeptides with functional domains from di¡erent origins and therefore exhibiting new biological properties. We have explored several permissive sites in Escherichia coli L L-galactosidase to generate functional hybrid enzymes displaying a mouse scFv antibody fragment. When this segment was placed at the amino-terminus of the enzyme, the whole fusion protein was stable, maintained its speci¢c activity and interacted speci¢cally with the target antigen, a ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
(38 reference statements)
0
5
0
Order By: Relevance
“…Despite the considerable advantages of the E . coli system for recombinant protein production, there are major technical hurdles like the formation of inclusion bodies as a consequence of high-level protein production with low amounts of active protein contained in insoluble aggregates in the cytoplasm [32]. This study had three aims related to Pvs 48/45: First, to optimize its expression using full-length codon harmonization.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the considerable advantages of the E . coli system for recombinant protein production, there are major technical hurdles like the formation of inclusion bodies as a consequence of high-level protein production with low amounts of active protein contained in insoluble aggregates in the cytoplasm [32]. This study had three aims related to Pvs 48/45: First, to optimize its expression using full-length codon harmonization.…”
Section: Introductionmentioning
confidence: 99%
“…When examining the combination of properties (cytoplasmic expression, affinity, melting temperature, and function in immunoassays for the detection of BclA), clone A5 was the best choice for construction of a β-gal fusion. Previously, researchers demonstrated that β-gal was tolerant to N-terminal fusions and could be produced genetically fused to a scFv for use in immunoassays [29]. We have expanded upon this prior work, demonstrating a functional genetic fusion between β-gal and an sdAb.…”
Section: Discussionmentioning
confidence: 92%
“…Additionally, β-gal is a tetramer with a molecular weight of 464 kDa, so fusions with this enzyme would also benefit from avidity. Previously, it had been reported that the enzyme β-gal is able to function with a scFv (linked variable heavy and variable light chain from a conventional antibody) inserted at the N-terminus of the enzyme [29]. Unlike fusions with AP, the β-gal fusions need to be produced in the cytoplasm.…”
Section: Introductionmentioning
confidence: 99%
“…As the recognition module of an antibody, the variable region (Fv) presents a stable scaffold composed of structurally conserved framework regions and highly divergent complementarity-determining regions. To date, many Fvs have been the target of protein engineering and are fused with other molecules or proteins to create novel molecular probes, sensor proteins, and fusion enzymes for prodrug therapy. …”
mentioning
confidence: 74%